Kokami Language Game to Improve Arabic Speaking Ability - Wulan Indah Putri (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2015)
There are four skills inside any languages, such as listening, speaking, reading and writing. In studying a foreign language we are led to be proficient in each skills. as well as the speaking skills. Language games used to facilitate students in understanding the material presented and making them more innovative to learn the language. One language games that are considered interesting in learning Arabic is KOKAMI (Box Mysterious Card). This game is one way of learning which requires students to learn a lot of talk and vocabularies. In addition students will be more enthusiasm as well as improving their speaking skills. Before learning starts, the first thing to do is to introduce vocabularies related with the material.